Assessing motivation for treatment in eating disorders: psychometric validation of the Italian version of the Autonomous and Controlled Motivation for Treatment Questionnaire (ACMTQ-ITA) - Silvia Tempia Valenta; Matilde Rapezzi; Federica Marcolini; Maurizio Speciani; Gabriele Giordani; Chiara De Panfilis; Diana De Ronchi; Anna Rita Atti (Eating and Weight Disorders, 2024)
Abstract Purpose Treatment resistance is a significant challenge in addressing eating disorders (EDs). The Autonomous and Controlled Motivation for Treatment Questionnaire (ACMTQ) has been previously validated in ED populations to assess patients’ motivation for treatment. This study aimed to validate the ACMTQ in the Italian language (ACMTQ-ITA) and evaluate its psychometric properties. Methods We recruited a clinical sample of adults aged 18 or older, diagnosed with EDs, proficient in the Italian language, and providing written informed consent. Participants with psychiatric comorbidities such as schizophrenia, bipolar disorder, and substance use disorder were excluded from the study. Validity of the ACMTQ-ITA was assessed using reliability analysis with Cronbach’s α and McDonald’s ω estimates, and Confirmatory Factor Analysis (CFA). Results Results from the reliability analysis confirmed the internal consistency of the Autonomous Motivation (AM) factor (α = 0.82, ω = 0.82), the Controlled Motivation (CM) factor (α = 0.76, ω = 0.77), and the ACMTQ-ITA overall score (α = 0.79). The CFA confirmed the two-factor solution (i.e., AM and CM) identified in the original validation of the ACMTQ (Comparative Fit Index = 0.92, Akaike Information Criterion = 3427.26, Bayesian Information Criterion = 3486.82; Root Mean Square Error of Approximation = 0.08, Standardized Root Mean Square Residual = 0.09). Conclusion The ACMTQ-ITA emerged as a valid and reliable tool for measuring motivation for treatment in individuals with EDs. Its implementation may facilitate the comprehension of treatment motivation, offering valuable clinical insights and implications for health management practices. Level of evidence: Level V, descriptive studies.